Exploration of the Counting Habit of the Hatam Tribe in Nuhuwei Papua Barat Indonesia - Wyrasti, Andi Fajeriani; Haryanto, Haryanto; Simamora, Ebeneser Wacner; Purwati, Purwati; Irnandi, Irfan; Firmansyah, Firmansyah; Siregar, Nahrun Najib; Ode, Abdul Syukur (Universitas Muhammadiyah Mataram, 2023)
The Hatam tribe is one of the sub-tribes of the Arfak tribe. This study aims to explore the numeracy culture of the Hatam Tribe spoken by the Hatam Tribe community who inhabit Nuhuwei Village, Ransiki District. This research is ethnographic. The techniques used for data collection are interviews, exploration, literature study, desk study, and documentation. Interviews and explorations were conducted with several elders who spoke the Hatam language in Nuhuwei Village. Literature and documentation studies were conducted by looking for other sources of information related to the previously existing Hatam language to obtain accurate results. The Desk Study was conducted to find out the mathematical patterns of the Hatam Tribe. The results obtained from this study are that mathematically, the counting patterns spoken by the Hatam people who inhabit Nuhuwei Village have different dialects from the speech of the Hatam people who inhabit other areas. Besides that, another finding is that the pattern of mentioning numbers spoken by the Hatam tribe inhabiting Nuhuwei Village correlates with the counting pattern on the Jarimatika. We call this latest finding related to counting using the Hatam language-based Jarimatika as Himatam (Calculating Using Jarimatika in the Hatam language). This finding shows that learning numeracy for elementary students in Nuhuwei Village can be done more easily using the Himatam Method.